New neotropical Epermeniidae (Lepidoptera). - Gaedike, Reinhard; Becker, Vitor Osmar (Contributions to Entomology = Beiträge zur Entomologie, 1989)
There were described on species of genus Epermenia and 4 species of Parochromolopis from Brazil and Mexico. The monophyly of Parochromolopis and its position within the subfamily Ochromolopinae is discussed. Nomenclatural Acts brasiliana Gaedike & Becker, 1989 (Epermenia (Calotripis)), spec. n. bicolor Gaedike & Becker, 1989 (Parochromolopis), spec. n. fuscocostata Gaedike & Becker, 1989 (Parochromolopis), spec. n. mexicana Gaedike & Becker, 1989 (Parochromolopis), spec. n. parva Gaedike & Becker, 1989 (Parochromolopis), spec. n.